Direct myocardial revascularisation: experience with 9364 operations. Issue 4 (August 1978) - Cooley, D A; Wukasch, D C; Bruno, F; Reul, G J; Sandiford, F M; Zillgitt, S L; Hall, R J
Abstract : Between July 1968 and December 1976, 9364 consecutive patients with coronary insufficiency underwent direct myocardial revascularisation using aortocoronary bypass (ACB). Among these patients 8017 had ACB alone, and the remaining 1347 had ACB in addition to correction of other cardiac and vascular lesions. In the series of patients having ACB alone the hospital (early) mortality was 3.9%, but for 2383 surgical patients in 1976 this figure was 2.2%. Operative mortality was higher for women (6.85%) than for men (3.5%), but late survival was about the same for both sexes. Among surviving patients 88% were improved or symptom-free after undergoing ACB. According to our data, at the end of eight years 80% of the patients will be survivors. These results, when compared with other series of patients treated medically, indicate the superiority of surgical treatment both in terms of symptomatic relief and also in increased life expectancy.